“A rua sabe quem é quem”: a comunicação do graffiti por meio da trajetória da VTS Crew na periferia de Fortaleza. - Campos, Fernanda de Façanha e (2020)
This research investigated graffiti and the projects produced by VTS Crew on the community of Fortaleza, trying to understand these interventions that are elaborated in Parque Dois Irmãos. The main objective is to analyze how communication happen in the city through the graffiti made by the VTS Crew with the realization of the Negras Raízes project and the graffiti made in the years 2018 and 2019 by the group. For this, we present the VTS Crew, a group composed of six graffiti artists (Mils, Vivi, Ane, Tubarão, Edi and Baga), created in 2005, who work in Parque Dois Irmãos, a neighborhood located on the outskirts of Fortaleza and in others neighborhoods in the city. The central question of this work sought to answer what graffiti in Fortaleza communicates through the production of graffiti and projects developed by VTS Crew on the outskirts of the city, especially in the Parque Dois Irmãos neighborhood.We question how the crew has been building, its relationship with graffiti since its origin and we contemplate the concept of crew with the authors Avramidis and Drakopoulou (2012). We bring a historical contextualization of graffiti in the contemporary context, in Brazil and VTS Crew. In theoretical terms, we also problematize the relationship between this expression and communication through the authors Campos (2010), Gitahy (2011) and Júnior (2014). In addition, we also reflected on the concept of identity, using the authors Hall (2006) and Bauman (2005). The methodology of the work is inspired by the ethnography in which we use Geertz (2008) and Malinowski (1976) as the main references. In addition, we also made use of ethnography on the internet through the monitoring of social networks, mainly the Instagram of the crew and their participants, in which we have as main reference Hine (2004; 2016). This investigation concluded about the importance of photographic and written documentation before the history of graffiti in Fortaleza, which has few records and the perception of social and cultural practices that this language allows to address. Regarding the VTS Crew, the group remains one of the main references in graffiti pioneering in Fortaleza and show that each year they seek to address new themes and techniques using graffiti. Keywords: Graffiti; VTS Crew; Communication in the city; Ethnography; Virtual ethnography.